DIFFERENCES ON STUDENTS' LEARNING ACTIVITIES IN THE MORNING SESSION AND THE AFTERNOON SESSION AT GRADE IV SD NEGERI 147 PEKANBARU - Dwi Nuraini; Eddy Noviana; Zetra Hainul Putra (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
School is one of the centers for learning activities administered to develop students’ potential. Students can  do various types of activities at school, such as : reading, writing, taking notes, asking questions, practicing, and expressing opinions. However, some schools administer the morning session and others administer the afternoon session. This study aimed to describe differences on the students’ learning activities at grade IV SD Negeri 147 Pekanbaru. The study was conducted through a qualitative method. Data were collected through observation while the techniques of data analysis were collecting data, reducing data, presenting data, and finally searching for conclusions. The results of this study showed that students attending the morning session performed more positive activities while students attending the afternoon session performed more negative activities. This research was expected to broaden the knowledge and insights of researchers in the field of education, particularly in students’ learning activities, and as a consideration for future researchers.